UPAYA MENINGKATKAN HASIL BELAJAR SISWAMATA PELAJARAN MATEMATIKA MATERI PERKALIANDAN PEMBAGIAN PECAHAN MELALUI METODE COOPERATIF LEARNING MODEL TGTKELAS VI SD NEGERI 1 KEDIRI - Bambang Sulistiono (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
The class action done by the researcher in this research is the useof Coorperation Learning model of TGT in Grade VI SD Negeri 1 Kediri. Thefindings of this TOD result is the improvement of student learning outcomesafter applying the TGT learning model from the initial average condition ofclass 62,69, the average cycle I 66,53 and the average cycle II 76,92. Then forclassical completeness from initial condition 46.15%, cycle I 53.85% and in cycleII to 76.92%. There is an increase, especially the classical completeness from theinitial to the first cycle is 7.7%, cycle I to cycle II is 23.07%.